Consuming Mung Beans (Phaseolus radiatus L.) Increase Hemoglobin Levels among Pregnant Women with Anemia in The Second Trimester at Klenang Public Health Centre, Probolinggo District - Tutik Hidayati; Roviatun Holila (Universitas Nahdlatul Ulama Surabaya, 2021)
Anemia in pregnancy is a pregnant mother with hemoglobin levels below 11g/dL in the first and third trimesters or hemoglobin levels less than 10.5 g/dLin the second trimester. This paper investigates the effect of consuming mungbeans (Phaseolus radiatus L.) on hemoglobin levels in the Second trimester ofpregnant women with anemia. This research used a quasi-experimental designwith randomized pretest-Posttest with a control group design. The populationwas 37 pregnant women in the second trimester who experienced anemia atKlenang PHC. Meanwhile, the sample was 34 respondents by simple randomsampling. The independent variable was consuming mung beans, while thedependent variable was the hemoglobin levels. In the control group, theauthors observed the consumption of Fe tablets once a day for 20 days in 17respondents. While in the intervention group, we monitored the consumptionof Fe tablets once a day and were given mung bean juice every day for 20days in 17 respondents. The instrument used an observation sheet and a digitalhemoglobin measuring device. Then, data analysis utilized the paired samplet-test with a significance of 0.05. After consuming mung beans and Fesupplements, the average hemoglobin levels in the intervention group were12.1588g/dL. Meanwhile, in the intervention group, after Fe observation were10.6412d/dL. There was a significant difference between the control andintervention groups p=0.000 (p<0.05). In conclusion, consuming mung beansincreases hemoglobin levels among pregnant women with anemia in thesecond trimester.